Bearing capacity of bolted ball-cylinder joint under uniaxial tensile force. (December 2020) - Guo, Xiaonong; Zeng, Qiang; Zhu, Shaojun; Huang, Zewei
Abstract: The bolted ball-cylinder (BBC) joint is a new type of joint system for non-purlin grid structures. Since the BBC joints may subject to tensile force in the cantilevered parts of the structure, or under situations where the wind suction dominates, this paper investigates the bearing capacity of the BBC joints under uniaxial tensile force by means of numerical analysis. Firstly, the establishment and verification of the finite element (FE) model is introduced briefly. Then, the parametric studies, considering various dimensions of the hollow cylinder, rectangular tube member, ribbed stiffener, convex washer, and high strength bolts are carried out based on the verified FE model, and the influence of each parameter is analyzed in detail. Finally, the formulae to estimate the bearing capacity of the BBC joint under uniaxial tensile force are obtained by regression analysis. The comparison of the calculation results using the formulae, the numerical and the experimental results shows that the proposed formulae are with satisfactory accuracy and can be applied to practical engineering.